2017
DOI: 10.1080/21655979.2016.1270808
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of φBT1-derived integrative plasmid pDZL802 in Amycolatopsis mediterranei U32

Abstract: The genus Amycolatopsis is well known for its ability to produce antibiotics, and an increasing number of valuable biotechnological applications, such as bioremediation, biodegradation, bioconversion, and potentially biofuel, that use this genus have been developed. Amycolatopsis mediterranei is an industrial-scale producer of the important antibiotic rifamycin, which plays a vital role in antimycobacterial therapy. Genetic studies of Amycolatopsis species have progressed slowly due to the lack of efficient tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Nocardia transformants allowed us to investigate individual insertion sites without any a priori knowledge of their location. Previous studies using ΦBT1 Int in Actinomycetes have determined insertion only by PCR around the known attB site (Gregory et al 2003;Li et al 2017), meaning that insertions at pseudo-attB sites would have been classed as "non-integrants" and most likely ignored. We sought to determine whether ΦBT1 pseudo-attB sites exist in various Streptomyces species and if these sites are utilised in strains with canonical attB sites.…”
Section: Identification Of Pseudo-attb Sites In Other Nocardia Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocardia transformants allowed us to investigate individual insertion sites without any a priori knowledge of their location. Previous studies using ΦBT1 Int in Actinomycetes have determined insertion only by PCR around the known attB site (Gregory et al 2003;Li et al 2017), meaning that insertions at pseudo-attB sites would have been classed as "non-integrants" and most likely ignored. We sought to determine whether ΦBT1 pseudo-attB sites exist in various Streptomyces species and if these sites are utilised in strains with canonical attB sites.…”
Section: Identification Of Pseudo-attb Sites In Other Nocardia Speciesmentioning
confidence: 99%
“…has also been reported, although this appears to occur relatively infrequently (Baltz 2012;Combes et al 2002). While vectors utilizing ΦBT1 Int have also been shown to integrate in a range of Streptomyces species and Amycolatopsis mediterranei, their usage outside these organisms has been limited (Gregory et al 2003;Li et al 2017). Furthermore, the extent to which ΦBT1 Int can catalyse integration at pseudo-attB sites is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While ΦC31 attB sites are highly similar in a number of Streptomyces species, non-specific integration in sequences that have partial identity to attB (pseudo- attB sites) has also been reported, although this appears to occur relatively infrequently ( Baltz, 2012 ; Combes et al, 2002 ). While vectors utilizing ΦBT1 Int have also been shown to integrate in a range of Streptomyces species and A. mediterranei , their usage outside these organisms has been limited ( Gregory, Till & Smith, 2003 ; Li et al, 2017 ). Furthermore, the extent to which ΦBT1 Int can catalyze integration at pseudo- attB sites is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ϕBT1 attB sites have been more commonly identified in Amycolatopsis , and there has been successful conjugative transfer of vectors based on ϕBT1 int/attP in A. orientalis(20) and A. mediterranei (21). Furthermore, electroporation remains the most widely applied method for transfer of integrative plasmids into this genus, rather than conjugation(20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…There is only one reported example of a conjugation system based on ϕC31 integrase in Amycolatopsis Japonicum MG4I7-CFI7(19), and it has been reported that other Amycolatopsis species lack ϕC31 attB sites in their chromosomes(20). The ϕBT1 attB sites have been more commonly identified in Amycolatopsis , and there has been successful conjugative transfer of vectors based on ϕBT1 int/attP in A. orientalis(20) and A. mediterranei (21). Furthermore, electroporation remains the most widely applied method for transfer of integrative plasmids into this genus, rather than conjugation(20, 21).…”
Section: Introductionmentioning
confidence: 99%